THE ROLE OF YOUTH IN MOTIVATION THROUGH SOCIALIZATION PROGRAMS ABOUT THE DANGERS OF DRUG ABUSE IN THE VILLAGE ENVIRONMENT TEMBUNG SUBDISTRICT PERCUT SEI TUAN DELI SERDANG REGENCY - Nur Aisyah; Dahrul Siregar (International Journal of Engagement and Empowerment, 2021)
The purpose of this community service activity is as follows. 1) Can improve the knowledge and understanding of youth about the types and dangers of drugs. 2) Can improve the skills of youth in tackling drug abuse. This devotional activity uses methods of lectures, discussions and demonstrations. The lectures given were presented in the form of PowerPoint presentations and demonstrating the dangers of Drugs. After that, a discussion/question and answer session ended with quizzical giving to motivate in improving and developing community service activities. The output obtained from this activity is the youth of Tembung Village, Percut Sei Tuan Subdistrict to know and understand how to tackle drugs so that youth can already make protection efforts against things that can lead to acts of drug abuse